ANALYSIS OF THE LEVEL OF KNOWLEDGE AND CONSUMER ATTITUDES TOWARDS THE DECISION TO CHOOSE WHITENING INFUSION BEAUTY IN RANTAUPRAPAT - Devi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Injection whitening in women's lives as a way to beautify themselves in the digital era is an ongoing trend. Seeing this condition, the level of knowledge and attitudes of consumers in choosing injection whitening as a solution for self-beautification is a phenomenon supported by reviews on business applications. The purpose of this study, among others, is to prove the level of knowledge and consumer attitudes towards one's decision to choose injection whitening. The sample in this study were students of the Faculty of Economics and Business, Labuhanbatu University TA 2023/2024 located in the city of Rantauprapat. The reasons for selecting a sample of female students include that the sample has the right criteria where, the respondent's status as a student, of course, has mentally had a good coginitive in assessing a new thing related to beauty health as many as 100 samples. The technique used in sampling is non probability sampling technique. Researchers used a purposive sampling technique, namely students of the Faculty of Economics and Business, University of Labuhanbatu, who were female and had heard of and used whitening injection as a beauty product. While the primary data of this research is an online questionnaire with google form. Data analysis to solve the relationship or influence of variables directly using SmartPLS. Based on the results of this study found that the variables of knowledge level and consumer attitudes affect a person's decision to use whitenin injection beauty products. Meanwhile, a person's decision to choose a beauty product in this digital era is strongly influenced by online customer reviews. It can be concluded that the level of public knowledge and consumer attitudes regarding beauty products, especially injection whitening, must be accurate and balanced. The author's suggestions for other researchers are expected to develop research on business strategies and consumer behavior regarding injection whitening as a lifestyle so that important information will be obtained as input for research development.